(untitled) (Economia Aplicada, 1999)
The present paper aims at giving an overview ofthe monetary framework presently known as inflation targets. It will be analyzed the historical context in which this framework first appeared, as well as its basic theoretical hypotheses as its differences from the classical regime ofmonetary targets. Next, we will discuss some practical aspects linked to the implementation and working ofinflation targets; for instance, the various forms of inflation measurements employed by the countries that adopt inflation targets. Special attention will be given to the model used by the English government. Finally, we will comment on some of the methodological problems faced by central banks that set targets on inflation, such as the uncertainty of their economic forecasts and the complex cause-effect relationships that hold among the economic variables. In the Brazilian case, a simple model of inflation under floating exchange rate and capital mobility will be outlined in order to stress the latter difficulties.